Comparação tecnológica, mineralógica e química da Formação Corumbataí em dois polos cerâmicos distintos visando sua aplicação na indústria de revestimentos cerâmicos - Christofoletti, S. R.; Moreno, M. M T [UNESP] (FapUNIFESP (SciELO), 2015)
The technological, chemical, mineralogical and ceramicvariations of Corumbatai Formation in three geological sections of two different ceramic clusters in the State of S. Paulo, Tambau/Porto Ferreira (T/PF) and Santa Gertrudes (SG), were studied,aiming to understand the variations that occur in these raw materials for product diversification. To study these variations, the methodology consisted of collection of geological sections, mineralogical analysis by X-ray diffraction in their full constitution and less than 2 Êm fraction, geochemical characterization for identification of major elements by ICP OES/MS, and ceramic tests for tiles.The chemical and mineralogical results directly influenced the ceramic characteristics. Sodium, which decreases the firing temperature and is found primarily in the sodic feldspar, is more abundant in the sections of Cluster SG than in sections of Cluster T/PF; this element acts during sintering together with the K of illites, but the potassic feldspar content is higher in the Cluster T/PF than in the SG; therefore, the available K can be lower. In addition to the clay minerals of the illite group, present in all samples, clay minerals of the smectite and kaolinite groups were identified. According to the results of ceramic tests, samples of the P-4 and P-11 sections of Cluster T/PF were classified as waterabsorbing group BIII (porous), and their most common application is the production of tiles with high porosity, or in tile formulationsfor dry and wet processes. Considering the samples of P-19 section of Cluster SG, the results were classified in groups BIb, BIIb and BIII enabling their application, particularly in the case of BIb and BIIb, for the tile production by dry process, or in mass compositions for the production of porcelain stoneware by wet route and porous bodies. These different results for the studied sections were directly affected by the type of feldspar, composition of main oxides, particle size, and different lithologies found in the geological sections.
Technological, mineralogical and chemical comparison of the Corumbataí Formation in two distinct ceramic clusters for applications in ceramic tile industry
Keywords: Ceramic; Clay; Corumbataí Formation